Standing Party Dalam Perspektif Islam, Kesehatan, Dan Budaya Indonesia - Solihah, Aida; Ryan, Virgillia; F, Hermin; Khoirul, Dini; H, Fauzan (Pena Medika Jurnal Kesehatan, 2019)
Food at an ordinary party is served in two ways, namely table service and standing party. Standing party emerged from the beginning of colonialism brought by the invaders who finally entered into the kingdoms in Indonesia. Standing party is a party where guests enjoy a variety of foods in a standing position. This standing position when eating is not very good from any perspective, therefore this journal is made. The method used is literature review sourced from blogs, books and journals. In the perspective of Islam, health, and Indonesian culture, stading parties have violated the rules. Islamic perspective, eating while standing deviated from the rules of al-hadith. From a health perspective, eating while standing can disrupt the process of human digestion. From the perspective of Indonesian culture, eating while standing deviates from the courtesy and ethics of Indonesian society. Therefore we discuss here the relationship between standing parties in Islam, health and Indonesian culture. Keyword: Standing party, food, Islam,health, culture